Studi Sistem Drainase Air Tambang Batubara di Sump Pit Bara4 PT Berkat Anugerah Sejahtera - Faras Dwi Putra; Salaho Dina Devy; Agus Winarno; Harjuni Hasan; Windhu Nugroho (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
Open-pit mining system mining is greatly influenced by surface runoff, rainwater and groundwater. This surface water runoff is highly dependent on rainfall catchment areas, climate, and land use. Handling surface water runoff entering the mining area by creating water channels in the form of open channels and closed channels. One of the mining methods that is generally carried out in Indonesia is the open-pit mining method, which is widely found in East Kalimantan. Large basins will be created as a result of this mining technique, which could eventually serve as a reservoir for water from both surface runoff and groundwater. Therefore, an analysis of the runoff water output in the sump is required, sump capacity and appropriate pumping ratio so that mining activities can continue. The results of the study obtained the runoff discharge value in the sump was 4,071.37 m3/day, the sump capacity was 207,474.07 m3, the water balance in the sump with a total runoff discharge of 5,871.37 m3/day, and the existing volume of water in the sump was 24,771 m3. evaporation of 4.36 m3/day, infiltration of 91.36 m3/day, and pump discharge of 8,229.27 m3/day. A pumping ratio of 0.71 was obtained.